«Auf dem Kopf gehen». The speech on madness in Georg Büchner’s Lenz (Itinera, 2023)
The essay aims to analyse Georg Büchner’s novel Lenz as a viable argument on madness that overturns the Cartesian perspective of Metaphysical Meditations. In the itinerary of the mind which leads the thinking subject to the self-understanding as res cogitans –  the “still and immobile” starting point for understanding the idea of God and thus unravellling the doubt about the very existence of the world and of its own corporeity – Descartes excludes madness considering it what is – and must remain – extraneous to thought so that through the exercise of doubt it can reach reliable knowledge that regulates man’s existence in the world and allows him to get out of doubt as to whether the world is a dream that does not exist ‘outside’ the mind.In this way, a human subject is outlined who does not know the suffering, nor does he experience the dramas of real existence, the fragility and vulnerability of finiteness. In the novel Lenz Büchner instead gives voice to a poet torn to the point of madness that suffers from doubt about the existence of God, of the world and of his own self. This leads to a discourse on madness as a pathological verse of human existence, a discourse that relates about the darkest parts of the human soul, that is, those eluding any clinical opposition between reason and madness and that represent, for this reason, an extraordinary trial for our main metaphysical categories.